Peningkatan Pengetahuan Ibu-Ibu Kajian Ummi Al Hijrah Mengenai Aktivitas Virus Mozaik Desease Pada Tanaman Cabai - Liss Dyah Dewi Arini; Nopita Cahyaningrum (Duta Abdimas, 2022)
Housewives have a myriad of activities, either as workers or employees or as housewives who prepare all household needs. Many things happen when mothers plant chilies at home, these plants do not bear fruit due to a virus attack. While most of the housewives have not seen the cause of their chili plants not bearing much fruit and dense. One of the causes of not bearing fruit or failed chili harvest is due to pests such as desease mosaic virus which causes chili plants to grow stunted, yellow leaves and bear little fruit or fail to bear fruit. On this occasion, the Implementer of Community Service for the D3 Medical Record and Health Information Study Program, Faculty of Health Sciences, Universitas Duta Bangsa Surakarta Surakarta has carried out P2M activities to study mothers Ummi Al Hijrah regarding the activities of the desease mosaic virus. On this occasion the executor of Community Service expressed his gratitude to the head of the Ummi Al Hijrah Study for giving permission to place to carry out Community Service activities. Hopefully this activity will be useful to increase the knowledge of the women of the Ummi Al Hijrah Study regarding the activity of the desease mosaic virus and its prevention so that they will pay more attention to environmental health. The output of this community service activity is that the study mothers of Ummi Al Hijrah can see symptoms, signs, and prevention of the desease mosaic virus that attacks chili plants. If the plant's body power has become immune, it is hoped that the accompanying disease can be prevented.